CONCENTRATIONS OF HEAVY METALS Pb, Cr, Cu and Zn IN DIFFERENT SIZE OF BLOOD COCKLE Anadara granosa FROM COASTAL WATER OF SINGKEP ISLAND LINGGA REGENCY RIAU ISLANDS PROVINCE - Darina Darina; Bintal Amin; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTARCT The research was conducted in January 2018 by collecting sample of blood cockle (Anadara granosa) from coastal water Sengkep Island, Lingga Regency of Riau Islands Province. The study used survey method and the samples were collected from the intertidal area directly by hand. The results of this study showed that Pb concentration was found to be highest in large size of the cockle in Station 1 (3,293 µg/g), the highest Cr and Cu concentrations were found in small size in Station 2 (2,124 and 2,733µg/g), and the highest Zn concentration was found in small size in Station 1 (46,875µg/g). The results also showed that MPI values obtained from coastal water of Singkep Island was 3,57.PTWI calculations derived from metal concentrations in both stations were 4,3837; 4,3435; 478,61 and 49,345 mg/kg/week for Pb, Cr, Cu and Zn respectively. The concentrations of heavy metals in cockle from coastal water of Singkep Island can be considered as safe and accordingly there is no risk for the human consumption of theses species as long as it does not exceed the suggested limit.Key words: Heavy metal, Pollution, Anadara granosa, PTWI, Singkep Island.